Pharmacy Technicians' Attention to Problems With Opening Medicine Packaging. (February 2014) - Philbert, Daphne; Notenboom, Kim; Koster, Ellen S.; Fietjé, Esther H.; van Geffen, Erica C. G.; Bouvy, Marcel L.
Background: Pharmacy technicians seem to be well equipped to engage in conversations with patients about their experiences and problems with medication, but it is unclear whether or not they systematically explain or demonstrate to patients how to use medication packaging.Objective: To explore to what extent pharmacy technicians identify problems with opening medicine packaging and how they assist patients in solving these problems.Methods: We conducted a cross-sectional study that comprised semistructured interviews, with 31 pharmacy technicians in 31 pharmacies, to assess the occurrence and type of difficulties with packagings and to suggest solutions.Results: All pharmacy technicians recognize the occurrence of packaging problems, though patients rarely report them at the pharmacy counter. Not all pharmacy technicians are familiar with opening all packaging forms, but they all describe ways to find out how to open them, which usually only happens after patients bring up problems. Solutions suggested by the pharmacy technicians include informing and counseling, changing or manipulating the packaging, and providing assisting tools.Conclusions: This study shows that although pharmacy technicians are aware that medication packaging can cause problems and are able to name or find out solutions to all these problems, there is no systematic attention for packaging at drug dispensation in most pharmacies. Discussing the handling of medication packaging should become a fixed part of drug dispensation counseling. Pharmacists should draw up working procedures to support pharmacy technicians in their counseling activities.